Management of post-transplant Epstein-Barr virus-related lymphoproliferative disease in solid organ and hematopoietic stem cell recipients - Marques,Heloisa Helena de Sousa (2014)
Epstein-Barr virus (EBV)-related post-transplant lymphoproliferative disease (PTLD) is one of the most serious complications associated with solid organ and hematopoietic stem cell transplantation. PTLD is most frequently seen with primary EBV infection post-transplant, a common scenario for pediatric solid organ recipients. Risk factors for infection or reactivation of EBV following solid organ transplant are stronger immunosuppressive therapy regimens, and being seronegative for receptor. For hematopoietic stem cell transplantation, the risk factors relate to the type of transplant, human leukocyte antigen disparity, the use of stronger immunosuppressants, T-cell depletion, and severe graft-versus-host disease. Mortality is high, and most frequent in patients who develop PTLD in the first six months post-transplant. The primary goal of this article is to provide an overview of the clinical manifestations, diagnosis, accepted therapies, and management of EBV infection in transplant recipients, and to suggest that the adoption of monitoring protocols could contribute to a reduction in related complications.